THANI: aplicación de atención integral de salud del niño o niña menor de 5 años con enfoque cuidado para el desarrollo infantil - Mallqui Contreras, Luis David (2023)
Currently, in health establishments, a comprehensive health care card for children under 5 years of age is delivered to the mother, father or caregiver of the child who was evaluated, with all the results of the growth, development and follow-up control. of the national vaccine scheme, as well as the programming of the next appointment and other indications on children's health. For this reason, modern digital mothers have the problem of losing their card or forgetting on appointments, which is why they lose track of the health of their youngest son or daughter. Also, they forget the indications or advice that were provided in the care for the health care of their son or daughter. In this sense, the present project proposes THANI as a mobile application that allows them to keep track of growth control, development and vaccinations, as well as empower care for child development through activities related to play and communication, and a added value of generating a community on child development with shared experiences of the same users. All this to achieve a healthy, strong and happy boy or girl. Regarding the results, the THANI MVP was tested and validated by users through the UX survey, where they indicated that the THANI application is easy to use, interesting, creative and innovative, therefore, they would use the application.